Developing Higher Berth Productivity: Comparison of Eastern Adriatic Container Terminals - Bojan Beškovnik (Promet (Zagreb), 2019)
This paper analyses changes of berth infrastructure and suprastructure by global container terminals (CTs) and by four eastern Adriatic ports in the last decade. The emphasis is on understanding whether CTs at Koper, Trieste, Rijeka and Bar achieved higher berth utilisation and productivity per ship-to-shore (STS) crane and if so, how and whether their development is in line with the global trend in CT berth productivity. On this basis a comparison model of twenty selected global CTs is used for productivity comparison as a first step in the process of analysing subsystem productivity. The study shows that four eastern Adriatic ports made different decisions, but with the same goals in reaction to the increased flow of containers via the Adriatic Sea transport route. Their main goal was to increase berth productivity by controlling the eventual subsystem overcapacity. According to observations, the Port of Koper is running at the subsystem’s upper level, while CTs in Trieste, Rijeka and Bar operate with certain degree of berth infrastructural, and suprastructural overcapacity.